Vesicle-associated membrane protein 5 is an intrinsic defense factor for embryonic stem cells against coronaviruses - Dong, Huijun; Pan, Zihang; Jiao, Pengtao; Ye, Fei; Peng, Qi; Yu, Yanying; Lai, Xinyuan; Li, Huan; Guan, Zhao; Deng, Juan; Shen, Tao; Tan, Wenjie; et al. (Nature communications, 2025)
Embryonic stem cells (ESCs) display a distinctive resistance against various viruses, irrespective of any interferon response. Nevertheless, the underlying mechanism of this resistance remains unclear. In this study, we identify vesicle-associated membrane protein 5 (VAMP5) as a potent cell-autonomous defense factor against coronaviruses, including SARS-CoV-2, with high expression levels observed in ESCs and mesoderm. VAMP5 not only exhibits functional conservation in restricting the replication of SARS-CoV-2 and its variants, as well as other highly pathogenic coronaviruses, but also shows efficacy in combating the replication of viruses from other families. Mechanistic investigations reveal that VAMP5 localizes to double membrane vesicles (DMVs) and impedes viral replication by relying on its vesicle-side C-terminal domain to interact with the viral non-structural protein 8 (NSP8), thus inhibiting the synthesis of negative-strand RNA. Our research demonstrates that VAMP5 in ESCs disrupts the protected environment of DMVs, which is essential for viral genome replication, and interacts with RNA replication complexes to defend against viral infection. This provides a novel strategy for developing broad-spectrum antiviral treatments. Stem cells are highly resistant to viral infection, irrespective of any interferon response. Here the authors discover that VAMP5 as a potent cell-autonomous defense factor protects ESCs from various viruses’ infection, including SARS-CoV-2 by interacting with RNA replication complexes to defend against viral infection.